Production Performance Of Emu Breeders - Boopathi, V.; Sivakumar , T.; Gnanaraj, P.Tensingh (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The present study was undertaken to assess the production performance of Emu breeders maintained in pair mating under semi intensive system during 2007-08 and 2008-09 laying seasons by adopting normal feeding management system on pilot basis. The mean number of eggs during 2007-08 and 2008-09 laying period was 69.8 and 147.25 days respectively. The mean egg production per bird in 2007-08 was 19.4 eggs and in 2008-09 were 40.5 eggs. The highest egg production per bird was 27 and 48 in 2007-08 and 2008-09 laying season. The best egg producer in the unit laid 48 eggs in a laying period of 177 days attaining a frequency of one egg in every 3.5 days. The mean Emu egg weight during the study period was 566.63±9.06 g.
Keywords: semi intensive system; laying season; egg weight; Emu breeders